Dehumidifying characteristics of air conditioner with reheating coil under mild and humid conditions. (September 2021) - Zhou, Feng; Liu, Yu; Zhao, Yaqian; Ma, Guoyuan
Highlights: An air conditioner with reheat coil was proposed. Thermal and dehumidification performances were tested. The system can work steadily under air condition mode, dehumidification mode 1 and mode 2. Dehumidification mode 1 has an obvious effective on heating and dehumidifying. Dehumidification mode 2 owns large moisture-removal capacity and low power. Abstract: As the conventional dehumidification process in an air conditioner is by subcooling the air, the supply air is insufficient to meet the indoor comfort needs under a mild and humid operating condition. This paper proposed an air conditioner with reheating coil and studied its working performance for varied compressor frequencies under different temperature and humidity conditions, including the supply air parameters and dehumidifying characteristics. As the results shown, the air conditioner with reheating coil worked steadily under air conditioning mode and two dehumidification modes. Other than conditioning the temperature only, it can also regulate the temperature with dehumidification. The largest temperature rise in the supply air was 8.45 °C compared with the inlet air, and the relative humidity was lowered by 51.88%, which indicated that the air conditioner with reheating coil worked sufficient under cold and humid or mild and humid weather. The specific moisture extraction rate increased with the rise of the inlet air temperature and relative humidity, but decreased along with the increase of compressor frequency. The maximum value of the specific moisture extraction rate reached 10.07 kg/kWh.